''Conservative revolutionaries'' : the Protestant and Catholic churches in Germany after radical political change in the 1990s - Thériault, Barbara (Monographs in German history, 2004)
During the forty years of division, the Protestant and Catholic churches in Germany were the only organizations to retain strong ties and organizational structures: they embodied continuity in a country marked by discontinuity. As such, the churches were both expected to undergo smooth and rapid institutional consolidation and undertake an active role in the public realm of the new eastern German states in the 1990s. Yet critical voices were heard over the West German system of church-state relations and the public role it confers on religious organizations, and critics often expressed the id.